Construção e validação de um material didático instrucional de um programa de educação permanente para enfermeiros assistenciais de terapia intensiva adulto - Gutierres, Franciele Aparecida (Universidade do Vale do Rio dos Sinos, 2018)
Because it is a complex and specialized environment for the care of critically ill patients, intensive therapy has at its disposal a variety of advanced technological resources. To handle these inputs, it is necessary a professional that presents both technical and scientific knowledge, according to the expertise of this area. However, the general training of graduations does not always provide sufficient subsidies for this. The application of active methodologies to facilitate and promote the qualification of these specialized nurses is a current concern, since these seek to transform the student into an active part in the educational process. Educating "at the" and "for" work is the proposal of permanent education in health, leading the individual to problematize everyday actions. To construct, develop and validate a didactic and instructional material for the application of a Permanent Education Program for Adult Intensive Care Nurses. A methodological study developed by the application of the Delphi (relevance) method and IVC (content validation index) to verify its validity and reliability. The program content was evaluated by expert judges (Lato sensu) with five years or more of work in the intensive care area. The product generated by this study (guideline) presented a total IVC of 0.99 (national and local scope), which is a value above that desired for validation of professional judges. It was concluded that the present research resulted in the development of a didactic-pedagogical tool, presented in guidance format format (product) for the application of a Permanent Education Program for Adult Intensive Care Nurses, which was proposed. It is suggested that this Permanent Intensive Care Education Program be evaluated for its practical applicability in subsequent research, in order to serve as a basis for specialization processes, seeking to expand the professional preparation of the intensive care nurse.
Keywords: Educação continuada; Tecnologia educacional; Enfermagem; Cuidados críticos; Material didático e instrucional; Continuing education; Educational technology; Nursing; Critical care; Instructional and instructional materials; ACCNPQ::Ciências da Saúde::Enfermagem